Analysis of Tooth Surface Wear Characteristic of Cylindrical Gear with Variable Hyperbolic Circular-arc-tooth-trace - Yongqiao Wei; Zhi Lian; Yongping Liu; Rui Guo; Jianquan Zhang (Jixie chuandong)
Gear wear is the the main failure form， the study of wear characteristics is instructive to the active design of cylindrical gear with variable hyperbolic circular-arc-tooth-trace（VH-CATT）. Based on Hertz contact theory and Archard wear calculation formula， the wear model of VH-CATT cylindrical gear is established， and the wear law at each point of tooth surface considering working condition parameters and design parameters are analyzed by numerical calculation. The analysis results show that the tooth surface wear of VH-CATT cylindrical gear pair decreases firstly and then increases from tooth root to tooth tip along the tooth profile direction， and the wear amount in tooth root is greater than that in tooth tip area， and the wear amount in pitch circle area is the smallest. It is distributed symmetrically along the tooth width direction， with the largest wear in the middle section and decreasing in turn from the middle section to the two end faces. The above research can provide theoretical basis for failure studies and life prediction of cylindrical gear with variable hyperbolic arc tooth line.